Combination of Intravesical Bacille Calmette-Guérin and Chemotherapy vs. Bacille Calmette-Guérin Alone in Non-muscle Invasive Bladder Cancer: A Meta-Analysis - Huang, Di; Jin, Ying-Hui; Weng, Hong; Huang, Qiao; Zeng, Xian-Tao; Wang, Xing-Huan (Frontiers in Oncology, 2019)
Background: About 75% of newly diagnosed bladder cancer cases suffer from non-muscle invasive bladder cancer (NMIBC), which used to recur and progress despite transurethral resection of bladder tumor (TURBT). This meta-analysis was conducted to examine if combined application of intravesical bacille Calmette-Guérin (BCG) with chemotherapy is associated with better prognosis. Methods: Systematic searches of randomized controlled trials (RCTs) concerning NMIBC were performed in PubMed, EMbase, CENTRAL, CNKI, WanFang, VIP, CBM databases and some specialized websites. Two researchers independently implemented study selection, quality assessment and data extraction. Hazard ratios (HRs) and their 95% confidence intervals (CIs) for treatment effects on recurrence-free survival (RFS), progression-free survival (PFS), overall survival (OS) and disease-specific survival (DSS) were directly extracted, if available, or estimated using relevant data from included studies. Side effects (SEs), such as fever, gastrointestinal reaction, cystitis, irritative bladder symptoms and hematuria, were also extracted as outcome measurements, and associated relative risks (RRs) were calculated to assess treatment safety. RevMan 5.3 software was used to perform statistical analyses. Results: Thirteen studies containing 1,754 patients with NMIBC were included in this meta-analysis. Compared with BCG alone, the combination therapy significantly improved RFS (HR=0.53, 95% CI: 0.43-0.66, P<0.01), OS (HR=0.66, 95%CI: 0.50-0.86, P=0.002) and DSS (HR=0.48, 95%CI: 0.29-0.80, P=0.005). While PFS showed no obvious difference between combination therapy and BCG alone (HR=0.65, 95%CI: 0.25-1.68, P=0.38). The rate of fever (RR=0.50, 95%CI: 0.27-0.91, P=0.02), irritative bladder symptoms (RR=0.69, 95%CI: 0.52-0.90, P=0.007) and hematuria (RR=0.50, 95%CI: 0.28-0.89, P=0.02) were significantly decreased in patients treated with combination therapy compared to those with BCG alone. There were no statistically significant differences between combination therapy and BCG alone in toxicity (RR=0.69, 95%CI: 0.34-1.40, P=0.30), gastrointestinal reaction (RR=2.54, 95%CI: 0.61-10.60, P=0.20) or cystitis (RR=0.67, 95%CI: 0.29-1.54, P=0.34). Conclusions: Combined application of intravesical BCG and chemotherapy appears to be an effective treatment for patients with NMIBC, but not for those with tumor in situ (Tis) alone or recurrent bladder cancer.